2008
DOI: 10.1073/pnas.0808048105
|View full text |Cite
|
Sign up to set email alerts
|

A mutant GlnD nitrogen sensor protein leads to a nitrogen-fixing but ineffective Sinorhizobium meliloti symbiosis with alfalfa

Abstract: The nitrogen-fixing symbiosis between rhizobia and legume plants is a model of coevolved nutritional complementation. The plants reduce atmospheric CO 2 by photosynthesis and provide carbon compounds to symbiotically associated bacteria; the rhizobia use these compounds to reduce (fix) atmospheric N 2 to ammonia, a form of nitrogen the plants can use. A key feature of symbiotic N 2 fixation is that N2 fixation is uncoupled from bacterial nitrogen stress metabolism so that the rhizobia generate ''excess'' ammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 51 publications
(62 reference statements)
5
27
0
5
Order By: Relevance
“…2. A similar phenotype was observed in Rm1021⌬glnB mutants (45). These data indicate that deletion In enteric bacteria, GlnK is crucial for the ability of cells to survive nitrogen starvation and resume rapid growth when fed ammonia (11).…”
Section: Free-living Phenotype Of An Rm1021⌬glnk Deletion Mutantsupporting
confidence: 64%
See 3 more Smart Citations
“…2. A similar phenotype was observed in Rm1021⌬glnB mutants (45). These data indicate that deletion In enteric bacteria, GlnK is crucial for the ability of cells to survive nitrogen starvation and resume rapid growth when fed ammonia (11).…”
Section: Free-living Phenotype Of An Rm1021⌬glnk Deletion Mutantsupporting
confidence: 64%
“…Supplementation of the media with 0.5, 1, or 2 g/liter glutamine and/or glutamate did not improve the growth of the Rm1021⌬glnK⌬glnB mutants. This is in contrast to Rm1021⌬ glnD-sm2, which grew much more normally on a favorable nitrogen source, such as glutamine (45). The growth defect of enteric bacteria lacking GlnB and GlnK proteins resulted from inhibition of serine biosynthesis (12).…”
Section: Free-living Phenotype Of An Rm1021⌬glnk Deletion Mutantmentioning
confidence: 68%
See 2 more Smart Citations
“…Since these genes encode proteins that regulate glutamine levels in the cell (40), we assayed glutamine for its ability to alter EI Ntr activity. These assays showed that glutamine was a potent inhibitor of EI Ntr , likely coupling the activity of the PTS Ntr to a critical signal of nitrogen levels in both free-living and symbiotic S. meliloti (40 (11). EI Ntr balances this activation against the glutamine availability in the cell, resulting in an intimate link between the availability of carbon and nitrogen.…”
Section: Discussionmentioning
confidence: 99%